Association between Leptin, Metabolic Factors and Liver Histology in Patients with Chronic Hepatitis C - Robert P Myers; Djamila Messous; Thierry Poynard; Francoise Imbert-Bismut (Canadian Journal of Gastroenterology)
BACKGROUND: Steatosis is common in hepatitis C virus (HCV)-infected patients and likely accelerates fibrosis progression. Leptin, the peptide product of the obesity gene (ob), has been implicated in hepatic fibrogenesis; circulating levels of leptin correlate with body fat mass. The objective of the present study was to determine the clinical and histological correlates of serum leptin in HCV-infected patients, and to determine its utility in predicting liver histological lesions.